Cost-utility analysis of MR imaging-guided transurethral ultrasound ablation for the treatment of low- to intermediate-risk localised prostate cancer - Muhler, Paul; Akuamoa-Boateng, Dennis; Rosenbrock, Johannes; Stock, Stephanie; Müller, Dirk; Heidenreich, Axel; Galendi, Julia Simões Corrêa [UNESP] (BMJ, 2025)
Background Magnetic resonance-guided transurethral ultrasound ablation (MR-TULSA) is a new focal therapy for treating localised prostate cancer that is associated with fewer adverse effects (AEs) compared with established treatments. To support large-scale clinical implementation, information about cost-effectiveness is required. Objective To evaluate the cost-utility of MR-TULSA compared with robot-assisted radical prostatectomy (RARP), external beam radiation therapy (EBRT) and active surveillance (AS) for patients with low- to favourable intermediate-risk localised prostate cancer. Design, setting and participants A Markov model was developed targeting 60-year-old men diagnosed with low- to intermediate-risk localised prostate cancer over a time horizon of 40 years from the German Statutory Health Insurance (SHI) perspective. To assess the robustness of the results, deterministic and probabilistic sensitivity analyses were performed. Intervention Four different treatment strategies were compared: minimally invasive MR-TULSA, two definitive approaches (RARP and EBRT) and one observational strategy (AS). Outcome measurements and statistical analysis Outcomes were measured in overall costs, quality-adjusted life years (QALYs) and the incremental cost-effectiveness ratio (ICER). Results AS generated the highest number of QALYs (12.67), followed by MR-TULSA (12.35), EBRT (12.35) and RARP (12.20). RARP generated the lowest costs (€ 46 997) over one patient's lifetime, while MR-TULSA was a slightly more expensive alternative (€48 826). The incremental cost-effectiveness ratio (ICER) of AS compared with RARP was €11 600 per QALY and of MR-TULSA compared with RARP was €12 193 per QALY, while EBRT was dominated. At a willingness-to-pay of €20 000 per QALY, the probability of being cost-effective is 44% for AS, 25% for RARP, 25% for MR-TULSA and 6% for EBRT. Conclusions All treatment options for 60-year-old men diagnosed with low- to intermediate-risk localised prostate cancer are affected by considerable uncertainty. Accepting high follow-up costs by applying a higher willingness-to-pay, AS is the most favourable treatment option.
Keywords: Health Care Costs; HEALTH ECONOMICS; Prostate disease; Urological tumours